Analisis Kesalahan Siswa pada Pembelajaran Matematika Berdasarkan Teori Newman dalam Menyelesaikan Soal SPLDV - Uirma Isnani Anisa; Elfis Suanto; Putri Yuanita; Maimunah Maimunah (Universitas Pendidikan Mandalika, 2023)
This study aims to investigate student errors based on Newman's Theory when solving SPLDV questions. Newman's Theory classifies errors into five types: reading errors, understanding errors, transformation errors, process skill errors, and final answer errors. The qualitative descriptive method was used in this study. The research subjects were twenty-four students from class IX at SMPN 2 Kampar. Tests and interviews were used as data collection techniques. The instrument used was in the form of five test questions with proven validity. The data analysis technique of this research used data reduction, data presentation, and conclusion. The analysis of student errors when answering SPLDV questions revealed that 6.92% of students made reading mistakes, 11.84% made understanding mistakes, 17.16% made a transformation error, 32% made a process skill error, and 31.62% made a final answer writing error. The most common mistake students made was a process skill error of 32%.